Faktor Yang Berhubungan Dengan Kejadian Ulkus Kornea : Literatur Review - Laras Pratiwi, Astari; Suharmanto, Suharmanto; Taolin, Alberto (CV. Jasa Sukses Abadi, 2025)
Corneal ulcer is a pathological condition in the form of a lesion or defect caused by the loss of tissue discontinuity accompanied by infiltration, which can occur in the cornea, from the epithelium to the stroma. This literature review aims to describe the factors associated with the occurrence of corneal ulcers. This literature review describes the factors associated with the occurrence of corneal ulcers. Researchers use articles from Google Scholar and PubMed. The articles used are articles from the last 10 years from 2015-2025. Researchers use the keywords